Accumulation Rates during 1311–2011 CE in North-Central Greenland Derived from Air-Borne Radar Data - Karlsson, Nanna B.; Eisen, Olaf; Dahl-Jensen, Dorthe; Freitag, Johannes; Kipfstuhl, Sepp; Lewis, Cameron; Nielsen, Lisbeth T.; Paden, John D.; Winter, Anna; Wilhelms, Frank (Frontiers in Earth Science, 2016)
Radar-detected internal layering contains information on past accumulation rates and patterns. In this study, we assume that the radar layers are isochrones, and use the layer stratigraphy in combination with ice-core measurements and numerical methods to retrieve accumulation information for the northern part of central Greenland. Measurements of the dielectric properties of an ice core from the NEEM (North Greenland Eemian Ice Drilling) site, allow for correlation of the radar layers with volcanic horizons to obtain an accurate age of the layers. We obtain 100 a averaged accumulation patterns for the period 1311–2011 for a 300 by 350 km area encompassing the two ice-core sites: NEEM and NGRIP (North Greenland Ice Core Project). Our results show a clear trend of high accumulation rates west of the ice divide and low accumulation rates east of the ice divide. At the NEEM site, this accumulation pattern persists throughout our study period with only minor temporal variations in the accumulation rate. In contrast, the accumulation rate shows more pronounced temporal variations (based on our centennial averages) from 170 km south of the NEEM site to the NGRIP site. We attribute this variation to shifts in the location of the high–low accumulation boundary away from the ice divide.